A new species of Conocephalus (Orthoptera: Tettigoniidae: Conocephalinae) from Argentina with extraordinarily broad-band ultrasound calling song - Rubio, Lucas; Braun, Holger (Zootaxa, 2024)
Conocephalus tuyu sp. nov. belonging to Xenocerculus subgen. nov., is described from grassland among the sand dunes of the Atlantic coast of Buenos Aires Province. The unique species can be recognized by its extremely short wings, the reddish brown dorsal band, and the curious male cerci with a very long, inward-pointing spine at the tip. The entirely ultrasound calling song of the male shows an extraordinarily broad spectrum reaching 90 kHz. Ecology and possible distribution are discussed.